(untitled) - Hove, L. van (Singapore, 2001)
The physics course benefitted from the mathematical expertise of the lecturer, which is also apparent in this thesis. Without his own research as scaffolding, Van Hove could not have built the short and beautiful course which provided the participants with a solid, useful foundation in modern physics.The lecture notes are in French. If they had been in English they would have been published together with the translation of the thesis. The first three pages of the notes are reproduced at the end of this book.
Keywords: Phép biến đổi (Toán học),Transformations (Mathematics)